Impact of Household Food Security and Government Food Assistance on the Nutritional Status of PLHIV in Malang, Indonesia - Tri Nurhudi Sasono; Ainun Hurrotaini (Media Publikasi Cendekia Indonesia, 2026)
This study examined the relationship between household food security, the Ministry of Social Affairs’ ATENSI food assistance, and the nutritional status of people living with HIV (PLHIV) in WPA Turen, Malang, Indonesia. Conducted in November 2025, this cross-sectional quantitative study involved 110 ATENSI recipients. Data were collected via questionnaires and Body Mass Index (BMI) measurements, then analyzed using Chi-square tests. Most respondents were socio-economically vulnerable: 86.4% earned below IDR 3,000,000 monthly, and nearly half were unemployed. Nutritionally, 60.9% had normal status, 23.6% were underweight, and 15.5% were overweight. Furthermore, 65.5% considered the ATENSI assistance inadequate for their household needs. A significant association was found between household food security and nutritional status (p=0.005), showing that food-insecure PLHIV were more likely to be underweight. However, the relationship between ATENSI assistance and nutritional status was not significant (p=0.238), likely because the assistance is only distributed annually, limiting its long-term impact. In conclusion, while household food security critically determines PLHIV nutritional status, annual assistance is insufficient. The study recommends shifting to monthly or quarterly distributions, alongside food diversification, nutrition education, and economic empowerment programs to address underlying poverty and improve health outcomes.